AFFECTION IN NICHOLAS SPARKS’ DEAR JOHN - Billy Lampus; Ceisy Wuntu; Imelda Lolowang (Fakultas Bahasa dan Seni, Universitas Negeri Manado, 2022)
The aim of this research is to analyze the affection between John and Savannah In this study, the writers employ qualitative research in which the data gathered in form of words and quotations. In analysing this novel, the writers apply objective approach because this analysis will be only focused on the literary work itself without looking at the external aspects of the literary work. It means that the writers only pay attention to the internal parts of the story in the novel. The result of this research will be able to enlarge the reader ability in appreciating literary works and also it can deeper the knowledge of the next researchers.